Leading Causes of Preterm Delivery as Risk Factors for Intraventricular Hemorrhage in Very Preterm Infants: Results of the EPIPAGE 2 Cohort Study. Issue 1 (March 2018) - Chevallier, M.; Debillon, T.; Pierrat, V.; Delorme, P.; Kayem, G.; Durox, M.; Goffinet, F.; Marret, S.; Ancel, P.Y.
Abstract : ( Am J Obstet Gynecol . 2017;216(5):518.e1–518.e12) Advances in care have resulted in large decreases in mortality and disability rates for preterm infants. While significant reductions in the rates of cerebral palsy have been seen, there has been no similar reduction in intraventricular hemorrhage (IVH), which is aggravated by weaknesses in the germinal matrix, changes in cerebral blood flow, and coagulation problems. Although the association of postnatal factors with IVH have been studied, the fact that the condition occurs within a few days of delivery implies that perinatal causes may be more important. In particular, the effect of pregnancy complications has not been studied. This study compared the incidence of IVH with the primary causes of preterm delivery.